Isotopic evidence for the formation of 25-norhopanes via in situ biodegradation in the Permian Lucaogou shales, southern Junggar Basin. (January 2022) - Sun, Funing; Hu, Wenxuan; Zhang, Zhirong; Cao, Jian
Highlights: A series of 25-norhopanes occur with co-existing hopanes in the Lucaogou shales. Genetic relationship between 25-norhopanes and regular hopanes revealed by CSIA. Degree of in situ biodegradation varies between shales. 13 C-depleted hopanoids imply a substantial contribution from methanotrophs. Abstract: Extracts of a set of the Permian Lucaogou shales collected from the southern Junggar Basin in NW China were examined for their molecular compositions and compound-specific isotopic signatures. The distribution of n -alkanes, isoprenoids, steranes, hopanes (C27 to C34 ) and appearance of 25-norhopanes (C26 to C33 ) were found to vary between samples, indicating that different degrees of biodegradation occurred in the shale strata. The non-biodegraded sample showed a complete composition of n -alkanes and isoprenoids including pristane (Pr) and phytane (Ph). Moderately biodegraded shales were characterized by near-absence of n -alkanes, but Pr and Ph still showed noticeable contents; 25-norhopanes were not detected. Heavily biodegraded shale had imperceptible content of n -alkanes, isoprenoids and steranes, but a series of abundant 25-norhopanes appeared. Compound-specific isotopic data show negative δ 13 C values (−44.4‰ to −55.6‰) for the regular hopanes having the same carbon number in all the examined shales, indicating a substantial contribution of methanotrophs to the sediments. Moreover, the 25-norhopanes had consistent δ 13 C values to the corresponding regular hopanes, which are proposed to be their parent molecules. The distributional and isotopic signatures indicate the 25-norhopanes in the heavily biodegraded Permian Lucaogou shales were genetically formed during in situ biodegradation of the extractable bitumen when the strata were uplifted from depth and may have been linked to the incursion of meteoric water.